Hard road shoulder material capable of being constructed by using slip form

By using specific ratios of hard shoulder materials in synovial construction, the combination of tail dust, cement, sand and water, the environmental pollution and utilization problems of the tail end fine powder are solved, and efficient construction and material utilization are achieved, improving the improvement of Construction efficiency and pavement quality.

CN119161141APending Publication Date: 2024-12-20DEZHOU HIGHWAY ENG CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411058852.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The fine powder at the tail end is generated during the production process of the asphalt mixing station, resulting in environmental pollution and health risks. The existing technology has not been effectively utilized and processed, affecting construction efficiency and cost.

Method used

The synovial construction method was adopted to prepare hard shoulder material by proportioning 60-83 parts of tail dust, 8-31 parts of cement, and 9-20 parts of sand. The mortar consistency was 35cm-50cm, and the water-solid ratio was 0.22-0.35. The combination was carried out. Sand and coarse sand meet the compressive, flexural, impermeable, frost and friction resistance, and improve construction efficiency and material utilization.

Benefits of technology

It realizes efficient utilization of tail dust, reduces construction costs and environmental pollution, improves construction efficiency and pavement quality, meets the performance standards of hard shoulders, and improves the working speed and overall construction efficiency of the synovial machine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161141A_ABST
    Figure CN119161141A_ABST
Patent Text Reader

Abstract

The invention provides a hard road shoulder material capable of being constructed by using a slip form, which is prepared from the following components in parts by weight: 60 to 83 parts of tail dust, 8 to 31 parts of cement, 9 to 20 parts of sand and 15 to 50 parts of water, the mortar consistency value of the hard road shoulder material is 35 cm to 50 cm; the friction coefficient value of the hard road shoulder swing type is 46-55 BPN. According to the technical scheme, the concrete material with the ratio can meet corresponding standards of 28d compressive strength, 28d breaking strength, water seepage resistance, frost resistance and friction resistance, and the concrete material is matched with a slip form machine under the ratio to be used, so that the working advancing speed of the slip form machine can be increased on the basis of guaranteeing the integrity and smoothness of a pavement, and the service life of the slip form machine is prolonged. Moreover, the quality of the road shoulder is also improved, and the overall construction efficiency is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of road construction materials, and in particular to a hard shoulder material that can be constructed using a sliding film. Background Art

[0002] In the treatment of construction waste, the most difficult part to handle and the part that is most likely to cause air pollution is the tail fine powder (hereinafter referred to as tail dust). Tail dust is the tail fine waste generated in the process of producing hot mix asphalt in asphalt mixing plants and collected by bag dust removal. It mainly includes stone powder, soil, residues from aggregate drying system and heavy oil combustion, etc. The particle size of these dusts is mostly less than 0.075mm, which is very easy to float in the surrounding environment, not only polluting the environment, but also affecting the health of equipment operators.

[0003] Slipfilm construction is an efficient concrete construction technology that can increase construction speed, reduce costs, and ensure project quality. In highway projects, the most common process is cement concrete slipfilm construction, and occasionally plain soil slipfilm construction, but the addition and use of tail fine powder has not yet been seen. Summary of the invention

[0004] According to the present invention, in view of the problems existing in the above-mentioned prior art, a hard shoulder material that can be constructed using a sliding film is provided, which includes, by weight: 60-83 parts of tail dust, 8-31 parts of cement, 9-20 parts of sand, and 15-50 parts of water; the mortar consistency value of the hard shoulder material is 35cm-50cm; the pendulum friction coefficient value of the hard shoulder is 46-55BPN. By having the above-mentioned technical features, the concrete material using this ratio can not only meet the 28d compressive strength, 28d flexural strength, water seepage resistance, antifreeze performance, and anti-friction performance, but also meet the corresponding standards, and under this ratio, when used in conjunction with a sliding film machine, it can improve the working speed of the sliding film machine on the basis of ensuring the integrity and flatness of the road surface, and also improve the quality of the road surface, further improving the overall construction efficiency.

[0005] In some embodiments, the water-solid ratio of the hard shoulder material is 0.22-0.35. Thus, the solid-liquid ratio is properly adjusted to avoid the material being too thin or too thick. At the same time, the working performance of the material is controlled by the mortar consistency value, so that it can be smoothly cast into the desired shape without collapse and deformation, and will not affect the coordination with the sliding film machine, resulting in uneven discharge of the sliding film machine, affecting the paving quality and engineering quality of the road surface.

[0006] In some embodiments, the sand includes at least one of medium sand and coarse sand. Therefore, the medium sand has a filling and cementing effect, and can reduce the segregation and stratification phenomenon in the mixed material, thereby ensuring the uniformity of the mixed material; while the coarse sand has larger particles, the bite force between the particles is stronger, and the strength is higher when mixed with cement; and it can reduce the shrinkage deformation of the cement paste to a certain extent, thereby reducing the risk of cracks caused by shrinkage of the concrete.

[0007] In some embodiments, the cement includes at least one of PO42.5 and PO52.5. Thus, PO42.5 is a medium-strength cement, which has the characteristics of high early strength, short setting time, fast hydration and hardening speed, low water bleeding rate, small shrinkage rate, good wear resistance, etc. PO52.5 also has the characteristics of high early strength. In addition, it has good wear resistance, high impermeability and erosion resistance, stable performance, and is suitable for configuring high-performance and high-grade concrete.

[0008] Compared with the prior art, the present invention has the following effects:

[0009] 1. Improved construction efficiency. Compared with traditional mold construction, the construction method of the sliding film machine greatly simplifies the construction process, reduces the construction period, and improves the paving efficiency. The paving and forming of the hard shoulder is achieved by only continuously feeding the sliding film machine with materials according to the preset ratio and controlling the speed of the sliding film machine;

[0010] 2. It provides a method for the bulk utilization of tail dust from asphalt mixing plants. In terms of paving materials, tail dust not only accounts for the largest proportion, but also meets the response standard of hard shoulder, thus providing a new direction for the application of tail dust from asphalt mixing plants;

[0011] 3. Reduced costs. Since the hard shoulder only uses dust from the mixing station, cement, sand and water, the material cost is saved to a great extent.

[0012] It should be understood that the contents described in the summary of the invention are not intended to limit the key or important features of the embodiments of the present disclosure, nor are they intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 A schematic diagram of a new road construction method for a hard shoulder of a highway provided by a preferred embodiment of the present invention is shown;

[0014] Figure 2 A schematic diagram of a construction method for repairing an old hard shoulder road of a highway provided by a preferred embodiment of the present invention is shown.

[0015] Explanation of symbols

[0016] 1. Remove the original shoulder; 2. Clean and level; 3. Mix materials; 4. Feed materials; 5. Pave the hard shoulder; 6. Embossing operation; 7. Set expansion joints; 8. Sprinkle water for maintenance. DETAILED DESCRIPTION

[0017] Hereinafter, preferred embodiments (or implementation modes) of the present invention will be described in detail with reference to the accompanying drawings.

[0018] Figure 1 A schematic diagram of a new road construction method for a hard shoulder of a highway provided by a preferred embodiment of the present invention is shown, with reference to Figure 1 As shown, a construction method for a highway hard shoulder mainly includes the following steps:

[0019] Cleaning and leveling 2. Excavators can be used to clean the basic road surface in the shoulder area, and the height of the foundation should be 80-200mm away from the height of the middle road surface. Secondly, the garbage and protruding stones on the basic road surface need to be cleaned. The cleaning work can be carried out in sections according to the length of the construction area to avoid being affected by environmental factors again during the construction process, causing garbage to fall on the construction road surface, ensuring that the construction road surface is clean and flat. After cleaning the garbage and stones, the construction road surface is compacted to ensure that the foundation is stable and firm, reducing the occurrence of subsequent road collapse.

[0020] Mix materials 3, prepare concrete pavement materials used by the sliding film machine, including 60-83 parts of asphalt mixing plant tail dust, 8-31 parts of cement, 9-20 parts of sand, 15-50 parts of water, water-solid ratio maintained between 0.22-0.35, and mortar consistency value of 35cm-50cm, then put the proportioned materials into the mixing equipment for mixing. The mixing equipment can adopt a fixed mixing method according to the construction length, or a mobile mixing method to reduce the impact of the feeding on the efficiency of the sliding film machine.

[0021] Among them, mixing station tail dust mainly refers to the tail fine waste generated in the process of producing hot mix asphalt in asphalt mixing station and collected by bag dust removal, mainly including stone powder, soil, residues from aggregate drying system and heavy oil combustion, etc. These particles cannot be effectively collected and processed, and are very easy to fly into the surrounding environment, which not only pollutes the surrounding air quality, but also has adverse effects on the surrounding vegetation, buildings, and human health. Therefore, using mixing station tail dust as raw material not only provides a pollution-free way to use mixing station tail dust, but also greatly reduces the overall cost of the concrete material.

[0022] Cement can be at least one of P.O42.5 and P.O52.5, wherein P.O42.5 is a medium-strength cement, which has the characteristics of high early strength, short setting time, fast hydration and hardening speed, low water seepage rate, small shrinkage rate, good wear resistance, etc. P.O52.5 also has the characteristics of high early strength, in addition, it has good wear resistance, high anti-seepage and anti-erosion performance, stable performance, and is suitable for configuring high-performance and high-grade concrete. The specific cement used can be determined according to the specific pavement parameters required by the shoulder pavement.

[0023] Sand can be at least one of medium sand and coarse sand. Among them, medium sand has a filling and cementing effect, and can reduce segregation and stratification in the mixture, ensuring the uniformity of the mixture. Compared with fine sand, medium sand has larger particles and higher bonding properties, thereby improving the strength of concrete. Coarse sand has larger particles and stronger bite force between particles. It has higher strength when mixed with cement. It can also reduce the shrinkage deformation of cement paste to a certain extent, thereby reducing the risk of cracks caused by shrinkage in concrete. In some cases, the appropriate use of coarse sand can also reduce the amount of cement used.

[0024] Feeding 4. Determine the mixing method according to the construction length. If the construction length is within the range of 0-15 meters, a fixed mixing method can be used, and the mixed materials can be added into the feeding port of the sliding film machine through manual feeding to provide shoulder paving for the sliding film machine. If the construction length is greater than 15 meters, a concrete mixer truck can be used to continuously supply materials to the sliding film machine to ensure the continuous construction and movement of the sliding film machine, thereby ensuring the construction efficiency of the sliding film machine.

[0025] Pave the hard shoulder 5, start the sliding film machine, and make it move slowly along the planned path to ensure the stability of continuous discharge of concrete materials and the integrity and flatness of the demoulding of the shoulder area.

[0026] Among them, the traveling speed of the sliding film machine can be adjusted according to the ratio of materials, specifically controlled at 0-5.5m / min. Since concrete materials mixed with mixing station tail dust are used, and the particle size of the mixing station tail dust is mostly less than 0.075mm, and as the first proportion of concrete materials, the texture is finer than traditional concrete materials, and it is not easy to stick to the mold of the sliding film machine, which greatly improves the integrity and smoothness of the shoulder forming. Compared with traditional concrete materials, its advantages can indirectly increase the traveling speed of the sliding film machine and ensure the integrity and smoothness of the shoulder pavement forming.

[0027] Embossing operation 6. Within 10 minutes after the shoulder is paved, use embossing equipment to emboss the shoulder surface. Since the concrete material used for paving the hard shoulder is mixed with a large amount of dust from the mixing station, the friction coefficient of the road surface after maintenance is much lower than that of the traditional concrete road surface. Therefore, embossing can increase the friction coefficient of the road surface and ensure the safety of people walking and vehicles traveling. Generally, the friction coefficient of the hard shoulder after maintenance is 90-100BPN, which is much higher than that of the untreated hard shoulder surface.

[0028] Expansion joints 7 are set. After embossing, expansion joints need to be set along the length direction of the road surface and in the width direction of the hard shoulder. The interval length of the expansion joints is 5-8 meters, and the depth of each expansion joint is controlled at 1 / 2-1 / 3 of the overall thickness of the hard shoulder to prevent cracks in the road surface caused by climate temperature changes, thereby extending the service life of the road surface.

[0029] Watering maintenance 8. After the compression joint construction, select appropriate watering vehicles or tools according to the maintenance area and needs to ensure the normal operation of the watering system; the shoulder can be maintained by sprinkling water and laying film on the shoulder. After the watering is completed, check the wetness of the surface of the maintenance object to ensure that the expected moisturizing effect is achieved.

[0030] Figure 2 A schematic diagram of a construction method for repairing an old hard shoulder road of a highway provided by a preferred embodiment of the present invention is shown, with reference to Figure 2 As shown, a construction method for a highway hard shoulder mainly includes the following steps:

[0031] Remove the original shoulder and use mechanical equipment to dig out the shoulder area of ​​the original road surface, and make the height of the excavated road surface foundation 80-200mm from the road surface, and the width of the excavated shoulder is not less than 0.75m.

[0032] For cleaning and leveling, excavators can be used to clean the basic road surface in the shoulder area, and the height of the foundation should be 80-200mm away from the height of the middle road surface. The garbage and protruding stones on the basic road surface should be cleaned. The cleaning work can be carried out in sections according to the length of the construction area to avoid being affected by environmental factors again during the construction process, causing garbage to fall on the construction road surface, ensuring that the construction road surface is clean and flat. After cleaning the garbage and stones, the construction road surface should be compacted to ensure that the foundation is stable and firm, reducing the occurrence of subsequent road collapse.

[0033] Mix materials and prepare pavement materials used by the sliding film machine, including 60-83 parts of asphalt mixing plant dust, 8-31 parts of cement, 9-20 parts of sand, and keep the water-to-solid ratio between 0.22-0.35. Put the mixed materials into the mixing equipment for mixing.

[0034] For feeding, the mixing method is determined according to the construction length. If the construction length is within the range of 0-15 meters, a fixed mixing method can be used. Compared with the manual feeding method, the mixed materials are added into the feeding port of the sliding film machine for shoulder paving of the sliding film machine. If the construction length is greater than 15 meters, a concrete mixer truck can be used to continuously supply materials to the sliding film machine to ensure the continuous construction and movement of the sliding film machine, thereby ensuring the construction efficiency of the sliding film machine.

[0035] When paving the hard shoulder, start the slip film machine and make it move slowly along the planned path to ensure the stability of continuous material discharge and the integrity and flatness of the demoulding of the shoulder area.

[0036]

Reference Standard

[0037] According to the new version of "Highway Engineering Technical Standards" implemented in 2015, the standard for hard shoulders will be based on function, specifically: the width of the right hard shoulder of expressways and first-class highways with trunk functions is generally 3 meters, with a minimum of 1.5 meters. The width of secondary roads in towns and villages can be determined according to actual conditions, but the relevant performance parameters of the hard shoulder are not specifically calibrated. However, the hard shoulder is also a highway area and meets the relevant highway specifications, so the compressive strength, flexural strength, water seepage resistance coefficient, antifreeze performance, and anti-friction coefficient will be used as performance indicators to judge whether the hard shoulder is qualified. The following is a specific embodiment.

[0038] Flexural strength:

[0039] According to the Highway Cement Concrete Pavement Design Specification, the design strength of cement concrete should adopt the flexural strength at 28 days of age. The standard value of the material flexural strength required for each traffic load level shall not be lower than that specified in Table 1.

[0040] Table 1:

[0041]

[0042] A road material that can be constructed using a sliding membrane. Since this material does not belong to cement concrete, it is closer to cement-stabilized materials. In addition, this material is a low-strength solid waste recycling material and is only used for low-grade roads in towns, villages, etc., so it meets the light traffic load level and takes 4MPa as the reference standard.

[0043] Anti-friction performance:

[0044] China's current standards stipulate that the anti-skid ability of the road surface should be characterized by measuring the swing value BPN with a pendulum instrument or measuring the lateral force coefficient SFC with a friction coefficient measuring vehicle. When BPN is greater than 42, or SFC is less than 0.5, the anti-skid ability of the road surface is excellent. Since the road material constructed by this sliding film is only used in the hard shoulder area of ​​towns and villages, it is mainly used for convenient transportation such as people, bicycles, and electric vehicles. The traffic load is limited and the vehicle speed is limited, so the anti-friction property of the road surface is based on 40BPN as the standard.

[0045] Antifreeze performance:

[0046] The frost resistance of concrete is generally expressed in frost resistance grades. The frost resistance grade is determined by the maximum number of freeze-thaw cycles that a 28-day-old test block can withstand when the compressive strength decreases by no more than 25% and the mass loss does not exceed 5% after absorbing water and being subjected to repeated freeze-thaw cycles. GBJ50164-92 divides concrete into the following frost resistance grades: F10, F15, F25, F50, F100, F150, F200, F250, F300, etc., which respectively indicate that the concrete can withstand 10, 15, 25, 50, 100, 150, 200, 250 and 300 repeated freeze-thaw cycles. Concrete with frost resistance grade ≥ F50 is called frost-resistant concrete.

[0047] Since this material does not belong to cement concrete, it is closer to cement stabilized materials, that is, semi-rigid materials, and its antifreeze performance is inferior to that of cement concrete. Moreover, this material belongs to solid waste recycling materials with lower strength. The purpose is to use its low cost to build shoulder auxiliary structures with less bearing function of low-grade roads. According to GBJ50164-92, its antifreeze coefficient is F15 as a qualified reference.

[0048] Water resistance:

[0049] A road material that can be constructed with sliding membrane. Since it is not cement concrete, its anti-permeability test is mainly carried out by referring to the asphalt pavement permeability coefficient test method in the "Highway Roadbed and Pavement Field Test Regulations". The general design annual average permeability is required to be 0.5L / (s·m 2 ), the designed annual average permeability coefficient cannot exceed 2.0mm / s.

[0050] Embodiment 1:

[0051] According to weight, take 60 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0052] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 14.8MPa.

[0053] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.8MPa.

[0054] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0055] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0056] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0057] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 50.8 BPN. See Table 3 for specific data.

[0058] The speed of the sliding film machine is 0-5.7m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0059] Embodiment 2:

[0060] According to weight, take 70 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0061] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 15.3MPa.

[0062] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0063] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0064] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0065] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0066] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 48.6BPN. Specific data are shown in Table 3.

[0067] The speed of the sliding film machine is 0-5.8m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0068] Embodiment 3:

[0069] According to weight, take 83 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0070] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 14.9MPa.

[0071] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.1MPa.

[0072] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0073] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0074] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0075] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 46.4BPN. Specific data are shown in Table 3.

[0076] The speed of the sliding film machine is 0-5.87m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0077] Embodiment 4:

[0078] According to weight, take 75 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 10 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0079] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 18.56MPa.

[0080] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4MPa.

[0081] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0082] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0083] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0084] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 49.1BPN. Specific data are shown in Table 3.

[0085] The speed of the sliding film machine is 0-5.6m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0086] Embodiment 5:

[0087] According to weight, take 75 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0088] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 18.56MPa.

[0089] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4MPa.

[0090] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0091] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0092] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0093] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 53.9 BPN. See Table 3 for specific data.

[0094] The speed of the sliding film machine is 0-5.7m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0095] Embodiment 6:

[0096] According to weight, take 75 parts by weight of mixing station tail dust, 15 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0097] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 18.3MPa.

[0098] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0099] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0100] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0101] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0102] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 50.2BPN. Specific data are shown in Table 3.

[0103] The speed of the sliding film machine is 0-5.5m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0104] Embodiment 7:

[0105] According to weight, take 75 parts by weight of mixing station tail dust, 21 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0106] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 21.67MPa.

[0107] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0108] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0109] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0110] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0111] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 52.3BPN. Specific data are shown in Table 3.

[0112] The speed of the sliding film machine is 0-5.6m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0113] Embodiment 8:

[0114] According to weight, take 75 parts by weight of mixing station tail dust, 31 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0115] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 24.56MPa.

[0116] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.6MPa.

[0117] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0118] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0119] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0120] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 54.2BPN. Specific data are shown in Table 3.

[0121] The speed of the sliding film machine is 0-5.56m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0122] Embodiment 9:

[0123] According to weight, take 75 parts by weight of mixing station tail dust, 21 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.28.

[0124] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 21.98MPa.

[0125] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.3MPa.

[0126] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0127] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0128] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0129] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 53.6BPN. Specific data are shown in Table 3.

[0130] The speed of the sliding film machine is 0-5.64m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0131] Embodiment 10:

[0132] According to weight, take 75 parts by weight of mixing station tail dust, 21 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.35.

[0133] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 22.79MPa.

[0134] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.2MPa.

[0135] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0136] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0137] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0138] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 46.5BPN. Specific data are shown in Table 3.

[0139] The speed of the sliding film machine is 0-5.54m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0140] According to the test results in Table 3, the concrete materials meet the national road standards in terms of 28d compressive strength, 28d flexural strength, water seepage resistance, antifreeze coefficient and anti-friction coefficient. However, due to the use of a sliding film machine for road construction, the anti-friction coefficient is between greater than 46 and less than 55, which can meet the working speed of the sliding film machine at 0-5.5m / min, and ensure the integrity and flatness of the demoulding of the concrete materials, greatly reducing the manpower consumption of manual post-finishing. Compared with the working speed of 0-5m / min of the traditional sliding film machine, it greatly increases the work efficiency and the yield rate.

[0141] Comparative Example 1:

[0142] According to weight, take 25 parts by weight of 52.5 grade ordinary Portland cement and 70 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0143] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 53MPa.

[0144] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 7.1MPa.

[0145] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it was measured that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0146] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0147] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0148] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the friction coefficient of the hard shoulder material that can be constructed with a sliding film is 89.2BPN. Specific data are shown in Table 3.

[0149] The speed of the sliding film machine is 0-3.2m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0150] By comparing and analyzing the test results of Table 4 with those of Table 3, Comparative Example 1 is a traditional concrete material. The concrete material meets the national road standards in terms of 28d compressive strength, 28d flexural strength, water resistance, antifreeze coefficient, and anti-friction coefficient. However, the sand particle size is large, and after mixing with cement, the surface is rough. The friction coefficient after curing is much higher than that of the hard shoulder material after curing with concrete materials using mixing station tail dust, which limits the working speed of the sliding film machine and the flatness of the road surface. After the concrete material is demolded from the sliding film machine, its integrity and flatness are worse than those of the concrete materials in Examples 1-10, which increases the consumption of manual repair and reduces the overall construction efficiency.

[0151] Comparative Example 2:

[0152] According to weight, take 50 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0153] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 13.59MPa.

[0154] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 3.54MPa.

[0155] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0156] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0157] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0158] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 69.8 BPN. See Table 3 for specific data.

[0159] The speed of the sliding film machine is 0-5.1m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0160] By comparing and analyzing the test results in Table 4 and Table 3, it is found that compared with Example 1, the tail dust content of the mixing station of Comparative Example 2 is reduced, resulting in the 28d compressive strength of the concrete being lower than 14MPa, and the 28d flexural strength being lower than 4, which does not meet the pavement strength standard.

[0161] Comparative Example 3:

[0162] According to weight, take 70 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 30 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0163] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 23.5MPa.

[0164] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0165] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0166] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0167] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0168] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 81.2. Specific data are shown in Table 3.

[0169] The speed of the sliding film machine is 0-5.43m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0170] By comparing and analyzing the test results of Table 4 with those of Table 3, it is found that compared with Example 5, the tail dust content of Comparative Example 3 is reduced and the coarse sand content is increased, resulting in the friction coefficient of the road surface after maintenance being higher than 80, which limits the working speed of the sliding film machine, reduces the smoothness of the road surface, and generates burrs intermittently, requiring subsequent manual repair.

[0171] Comparative Example 4:

[0172] According to weight, take 70 parts by weight of mixing station tail dust, 40 parts by weight of 52.5 grade ordinary Portland cement, and 10 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0173] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 48.5MPa.

[0174] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 6.8MPa.

[0175] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0176] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0177] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0178] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 83.2. Specific data are shown in Table 3.

[0179] The speed of the sliding film machine is 0-5.3m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0180] By comparing and analyzing the test results of Table 4 with those of Table 3, it is found that compared with Example 4, the cement content of Comparative Example 4 is increased, resulting in increased compressive strength and flexural strength of the concrete, but also increasing the friction coefficient of the road surface, which limits the working speed of the sliding film machine, reduces the smoothness of the road surface, and generates burrs intermittently, requiring subsequent manual repair.

[0181] Comparative Example 5:

[0182] According to weight, take 70 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 10 parts by weight of coarse sand, with a water-to-solid ratio of 0.41.

[0183] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 24.5MPa.

[0184] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.7MPa.

[0185] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0186] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0187] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", it is measured that the strength loss of the hard shoulder material that can be constructed using a sliding film of the present invention after 15 freeze-thaw cycles is less than 25%.

[0188] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 50. See Table 3 for specific data.

[0189] The demoulding integrity rate of concrete materials is low and local collapse is prone to occur.

[0190] By comparing and analyzing the test results in Table 4 with those in Table 3, although the concrete material meets the national road standards in terms of 28d compressive strength, 28d flexural strength, water resistance, antifreeze coefficient and anti-friction coefficient, the increase in water-solid ratio causes partial collapse of the concrete pavement after demoulding during the operation of the sliding film machine, which reduces the integrity of the hard shoulder.

[0191] A road material that can be constructed using a sliding film. This material does not belong to cement concrete, but is closer to cement-stabilized materials, i.e., semi-rigid materials. Its antifreeze performance is inferior to that of cement concrete. This material is a solid waste recycling material with lower strength. The purpose is to use it to build shoulder auxiliary structures with less load-bearing functions of low-grade roads at a low cost. This material is only used in the shoulder area of ​​Class IV highways. With the sliding film construction process, a hard shoulder with high integrity, high flatness, and less manual repair is paved. The material is reasonably proportioned to control the friction coefficient of the hard shoulder between 46-55BPN, thereby increasing the travel speed of the sliding film equipment, and improving construction efficiency while ensuring quality.

[0192] Table 3:

[0193]

[0194] Table 4:

[0195]

[0196]

[0197] In the description of this specification, the terms "connection", "installation", "fixation" and the like should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0198] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A hard shoulder material that can be constructed using a sliding film, characterized in that: According to weight, it includes: 60-83 parts of tail dust, 8-31 parts of cement, 9-20 parts of sand, and 15-50 parts of water; The mortar consistency value of the hard shoulder material is 35cm-50cm; The pendulum friction coefficient value of the hard shoulder is 46-55BPN.

2. The hard shoulder material that can be constructed using a sliding film according to claim 1, characterized in that: The water-to-solid ratio of the hard shoulder material is 0.22-0.

35.

3. The hard shoulder material that can be constructed using a sliding film according to claim 1, characterized in that: The sand includes at least one of medium sand and coarse sand.

4. The hard shoulder material that can be constructed using a sliding film according to claim 1, characterized in that: The cement includes at least one of PO42.5 and PO52.5.